Monitoring of bisphenols in canned tuna from Italian markets. (September 2015) - Fattore, Margherita; Russo, Giacomo; Barbato, Francesco; Grumetto, Lucia; Albrizio, Stefania
Abstract: Monitoring of food contamination from bisphenols is a necessary process for the consumers' risk assessment. A method for the quali-quantitative analysis of Bisphenol A (BPA), Bisphenol B (BPB), Bisphenol A Diglycidyl Ether (BADGE), and Bisphenol F Diglycidyl Ether (BFDGE), by liquid chromatography with fluorescence detection (LC-FD), was performed and validated for their determination in 33 samples of tuna fish, canned in either oil or aqueous medium. Samples were collected in Italian markets. Tuna and the correspondent preservation medium were analyzed separately. Detected levels of bisphenols ranged from 19.1 to 187.0 ng/g in tuna matrix and from 6.3 to 66.9 ng/mL in oil medium. No bisphenols were found in aqueous medium. At least one of the analytes was found in 83% of the tuna samples in oil medium, whereas tuna samples in aqueous medium showed BPA alone in 67% of samples. 21% of the oil medium samples resulted positive for at least one bisphenol. On the basis of measured concentrations and general daily ingestion rate of canned tuna fish, the probable daily intake of BPA for Italian population was calculated. Graphical abstract: Highlights: BPA, BPB, BADGE and BFDGE monitored for Italian market canned tuna samples. 33 canned tuna samples and their respective preservation medium analyzed separately. Bisphenol levels in all positive samples below the legal limits.